Smart nutrition - Halula, Wes.; Nelson, Melanie; Halula, Jenica; Naumann, Jason; Learning Zone Express (Firm). ([California] : Learning Zonexpress, 2009)
Host Wes Halula and two teens set the facts straight about breakfast, body image, portion size, physical activity, the importance of fruits and vegetables, beverages, significant nutrients, late night snacking, vegetarian diets, and acne in this fun and entertaining video.
Host: Wes Halula; featuring Genevieve Helm and Ricky Castleberry.
Grades 6-adult.
DVD format.
Keywords: Nutrition; Exercise; Health